QUALITY OF LIFE AND FACTORS ASSOCIATED WITH PALLIATIVE CARE NEEDS AMONG PATIENTS WITH CHRONIC KIDNEY DISEASE UNDERGOING MAINTENANCE HEMODIALYSIS AT THUY NGUYEN MEDICAL CENTER (Vietnam Journal of Community Medicine, 2026)
Objective: (1) To describe the quality of life (QoL) of patients with chronic kidney disease (CKD) undergoing maintenance hemodialysis and (2) to identify factors associated with their palliative care needs.Methods: A cross-sectional study was conducted on 72 patients with end-stage renal disease (ESRD) undergoing periodic hemodialysis at Thuy Nguyen Medical Center. Data were collected using the VietPOS and EQ-5D-5L instruments.Results: Regarding QoL, the most significantly affected domain was pain/discomfort (69.4%), followed by anxiety/depression (48.6%) and mobility (47.2%). The mean EQ-VAS score was 62.3 ± 14.8. Factors significantly associated with higher palliative care needs included low income (p=0.031), smaller household size (p=0.048), high ECOG performance status (p=0.004), and low hemoglobin levels (p=0.022).Conclusion: Patient quality of life is substantially impaired, primarily by pain and discomfort. Palliative care needs are strongly influenced by economic factors, family support, and performance and anemia status.
Keywords: palliative care, quality of life, chronic kidney disease, periodic hemodialysis